2021
DOI: 10.1109/jsen.2020.3041023
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Sensor-Based Methodologies for Food Portion Size Estimation

Abstract: Food portion size estimation (FPSE) is critical in dietary assessment and energy intake estimation. Traditional methods such as visual estimation are now replaced by faster, more accurate sensor-based methods. This paper presents a comprehensive review of the use of sensor methodologies for portion size estimation. The review was conducted using the PRISMA guidelines and full texts of 67 scientific articles were reviewed. The contributions of this paper are threefold: i) A taxonomy for sensor-based (SB) FPSE m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 102 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…Thus, reducing any error is desirable. Also with increasing availability of wearable sensors (see [19]) there are opportunities for hybrid approaches combining direct (based on physical properties of food) and indirect (based on food intake activity) measures to reduce overall error. Future work will focus on improving the accuracy of the automated aspects of the approach, for example the accurate identification of corner markers that is critical to accurate 3D projection, and determining the impact of increased training [12] for improvements in the manual aspects, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reducing any error is desirable. Also with increasing availability of wearable sensors (see [19]) there are opportunities for hybrid approaches combining direct (based on physical properties of food) and indirect (based on food intake activity) measures to reduce overall error. Future work will focus on improving the accuracy of the automated aspects of the approach, for example the accurate identification of corner markers that is critical to accurate 3D projection, and determining the impact of increased training [12] for improvements in the manual aspects, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned manual methods are cumbersome, subject to memory (and therefore prone to error), and are not accurate compared to the much recent automatic assessment methods. A previous review [ 13 ] identified some of the existing image-based food portion size estimation (FPSE) methods that are automatic. It was seen that food portion size can be estimated automatically using food images captured during the meal [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…To monitor Sensors 2022, 22, 1493 2 of 17 the intake of energy and nutrients accurately, each food in the image must be identified and its volume estimated. Although food recognition has been extensively studied using deep learning techniques [11][12][13][14][15][16][17], estimating food volume from images remains a challenging problem [9][10][11]18]. Several sensor-based approaches have been reported [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Although food recognition has been extensively studied using deep learning techniques [11][12][13][14][15][16][17], estimating food volume from images remains a challenging problem [9][10][11]18]. Several sensor-based approaches have been reported [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. A special imaging sensor called a depth sensor has been used to produce depth on a per-pixel basis from which food volume can be estimated [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation